7 - The Academic Dean and the Challenges of Meeting Changing Expectations in a Competitive Higher Education Environment in Africa - Alfred Otara, (Journal of Higher Education in Africa, 2014)
This article seeks to provide guidelines for leadership decisions and prac- tices that university deans can follow to be effective in their institutions and be relevant in an increasingly competitive African milieu. The paper provides an overview of academic leadership by faculty deans and assesses the degree to which they demonstrate leadership in addressing contempo- rary challenges and expectations. The paper shows how academic leaders must hold and convey ideas and knowledge that could shape managerial thought and practice. It also emphasizes that they must develop a human resource network inside and outside their departments and university and at levels – be they local, national, and international. Academic leadership needs to have a structured approach to faculty and staff promotion and development, and it should be placed on a priority list. Deans need to use technology and communication channels effectively to improve access to knowledge. The educational programmes must be dynamic and streamlined to meet the demands of the job market as well as the aspirations of all the stakeholders, including the external stakeholders.